Fluororesin composition

JP2025027159AInactive Publication Date: 2025-02-27AGC INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2021209643
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2021-12-23
Publication Date
2025-02-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、難燃性及び耐薬品性に優れるフッ素樹脂組成物を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025027159000001
    Figure 2025027159000001
Patent Text Reader

Abstract

To provide a fluororesin composition excellent in flame retardancy and chemical resistance.SOLUTION: The fluororesin composition contains a fluororesin and an additive for imparting flame retardancy to the fluororesin. The additive is a carbon-containing inorganic material. The content of the additive is 0.0001-20 mass% based on the total mass of the fluororesin composition. The fluororesin composition has a limiting oxygen index of 35% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fluororesin composition. [Background technology]

[0002] Due to their high chemical resistance, fluororesins are used in many applications, such as cable covering materials, coating materials, and building structural materials. Fluororesins also have good flame retardancy, and are used in applications where flame retardancy is required. However, in recent years, there has been a demand for higher flame retardancy due to changes in the usage environment and amendments to related laws and regulations.

[0003] Patent Document 1 proposes a highly flame-retardant black ethylene-tetrafluoroethylene copolymer paint containing 95 to 99.5 parts by mass of ethylene-tetrafluoroethylene copolymer, 0.5 to 5 parts by mass of black pigment, and 5 to 20 parts by mass of flame retardant. Copper chrome black is used as the black pigment. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] China Patent Application Publication No. 111574890 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in order to obtain sufficient flame retardancy with the paint of Patent Document 1, the content of the flame retardant must be increased, and the content of the fluororesin must be relatively reduced, resulting in reduced chemical resistance.

[0006] The present invention provides a fluororesin composition having excellent flame retardancy and chemical resistance. [Means for solving the problem]

[0007] The present invention has the following aspects. [1] A fluororesin composition comprising a fluororesin and an additive that imparts flame retardancy to the fluororesin, the additive is a carbon-containing inorganic material, the content of the additive is 0.0001 to 20% by mass relative to the total mass of the fluororesin composition, A fluororesin composition having a limit oxygen index of 35% or more. [2] The fluororesin composition according to [1] above, having a tensile strength of 80% or more and a tensile elongation of 80% or more of the tensile strength of the fluororesin. [3] The fluororesin composition according to [1] or [2] above, wherein the mass loss rate when the additive is kept under an atmosphere of 28°C and 80% RH for 14 days and then heated in an oven at 150°C for 1 hour is less than 0.3% by mass. [4] The fluororesin comprises a partially fluorinated resin, The fluororesin composition according to any one of [1] to [3] above, wherein the partially fluorinated resin is contained in the largest amount of the fluororesins among all the fluororesins contained in the fluororesin composition. [5] The fluororesin comprises a copolymer having units based on tetrafluoroethylene and units based on ethylene, The fluororesin composition according to any one of [1] to [4] above, wherein the content of the copolymer is the highest among all the fluororesins contained in the fluororesin composition. [6] The fluororesin composition according to [5], wherein the copolymer has a hydroxyl group at an end of the main chain. Effect of the Invention

[0008] According to the present invention, it is possible to provide a fluororesin composition having excellent flame retardancy and chemical resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The meanings and definitions of the terms used in the present invention are as follows. The "Limiting Oxygen Index" (hereinafter referred to as LOI) is an oxygen index measured in accordance with JIS K 7201-2:2007. LOI is an index of the minimum oxygen concentration (volume%) required for a sample to sustain combustion, and the higher the index, the higher the flame retardancy. The "tensile strength" and "tensile elongation" are each determined by preparing a dumbbell-shaped test piece (thickness 1 mm) specified in JIS K 6251 from a sample (fluororesin composition or fluororesin) and conducting a tensile test on the test piece under conditions in accordance with JIS K 6251. "Melting point" is the temperature corresponding to the maximum of the melting peak as measured by differential scanning calorimetry (DSC). The term "melt moldable" refers to exhibiting melt flowability. The term "exhibiting melt fluidity" means that there exists a temperature at which the melt flow rate is 0.1 to 1000 g / 10 min under a load of 49 N at a temperature at least 20° C. higher than the melting point of the resin. "Melt flow rate" is the melt mass flow rate (MFR) defined in JIS K 7210:1999 (ISO 1133:1997). The term "unit based on a monomer" is a general term for an atomic group formed directly by polymerization of one monomer molecule, and an atomic group obtained by chemically converting a part of the atomic group. "Monomer" means a compound that has a polymerizable carbon-carbon double bond. The symbol "~" indicating a range of values ​​means that the values ​​before and after it are included as the lower and upper limits.

[0010] [Fluororesin composition] A fluororesin composition according to one embodiment of the present invention (hereinafter also referred to as the present composition) contains a fluororesin and an additive (hereinafter also referred to as additive B) that imparts flame retardancy to the fluororesin.

[0011] <Fluororesin> Examples of fluororesins include polymers having units based on at least one fluoromonomer selected from tetrafluoroethylene (hereinafter also referred to as TFE), hexafluoropropylene (hereinafter also referred to as HFP), perfluoro(alkyl vinyl ether) (hereinafter also referred to as PAVE), chlorotrifluoroethylene (hereinafter also referred to as CTFE), vinylidene fluoride (hereinafter also referred to as VdF), and vinyl fluoride.

[0012] The fluororesin may be a homopolymer having one type of unit, or a copolymer having two or more types of units. The fluororesin may further have a unit based on a non-fluorine monomer. Examples of the non-fluorine monomer include ethylene (hereinafter also referred to as E), propylene, itaconic anhydride, vinyl acetate, etc. When the fluororesin has a unit based on a non-fluorine monomer, the unit based on the non-fluorine monomer may be of only one type or of two or more types.

[0013] As the fluororesin, a melt-moldable fluororesin is preferred because the fluororesin composition has excellent moldability. Examples of melt-moldable fluororesin include a copolymer having units based on TFE (hereinafter also referred to as TFE units) and units based on E (hereinafter also referred to as E units) (hereinafter also referred to as ETFE), a copolymer having TFE units and units based on PAVE (hereinafter also referred to as PAVE units), a copolymer having TFE units and units based on HFP (hereinafter also referred to as HFP units), a copolymer having TFE units and units based on HFP (hereinafter also referred to as HFP units), a copolymer having TFE units, PAVE units and HFP units, a polymer having units based on CTFE, a copolymer having units based on CTFE and E units, and a polymer having units based on VdF. The MFR of the melt-moldable fluororesin is preferably from 0.1 to 70 g / 10 min, more preferably from 3 to 40 g / 10 min.

[0014] The melt-moldable fluororesin preferably has a melting point. The melting point of the fluororesin is preferably 160 to 325°C, more preferably 220 to 320°C, and even more preferably 250 to 270°C. When the melting point of the fluororesin is equal to or higher than the lower limit, the composition has excellent heat resistance and rigidity at high temperatures. When the melting point of the fluororesin is equal to or lower than the upper limit, the composition has excellent moldability.

[0015] The fluororesin preferably contains a partially fluorinated resin as a main component. The term "mainly contains" means that the content is the highest among all the fluororesins contained in the composition. A partially fluorinated resin is a fluororesin that contains hydrogen atoms, and has superior mechanical properties compared to a fully fluorinated resin that does not contain hydrogen atoms, but tends to have inferior flame retardancy. Therefore, the present invention is highly useful when the fluororesin contains a partially fluorinated resin as a main component. The fluororesin may further contain a fully fluorinated resin. The content of the partially fluorinated resin is preferably 50% by mass or more, more preferably 80% by mass or more, and may be 100% by mass, based on the total mass of the fluororesin.

[0016] Examples of partially fluorinated resins include polymers having units based on a fluorine monomer containing a hydrogen atom, and polymers having units based on a fluorine monomer and units based on a non-fluorine monomer. In the partially fluorinated resin, the mass ratio of hydrogen atoms to fluorine atoms (hydrogen atoms / fluorine atoms) is preferably 10 / 90 to 1 / 99, and more preferably 6 / 94 to 2 / 98. When the hydrogen atoms / fluorine atoms ratio is equal to or more than the lower limit, the resin has excellent heat resistance, chemical resistance, and flexibility, and when it is equal to or less than the upper limit, the resin has excellent mechanical properties.

[0017] As the partially fluorinated resin, ETFE is preferred because it is excellent in moldability, electrical properties, mechanical properties, abrasion resistance, and the like. As ETFE, a copolymer having E units, TFE units, and units based on monomers other than ethylene and TFE (hereinafter also referred to as "other monomer units") is preferred, because it has even more excellent heat resistance, mechanical properties, and chemical resistance.

[0018] The other monomer may be any monomer capable of copolymerization with ethylene and TFE, and examples thereof include the compound represented by the formula 1 described below, the above-mentioned fluorine monomer (excluding TFE), and non-fluorine monomer (excluding ethylene). One type of other monomer may be used alone, or two or more types may be used in combination.

[0019] The other monomer units preferably contain a unit based on a compound represented by the following formula 1 (hereinafter also referred to as FAE) in terms of better mechanical properties and thermal stability. CH2=CX(CF2) n Z expression 1 Here, X and Z each independently represent a hydrogen atom or a fluorine atom, and n is an integer of 1 to 10.

[0020] X in formula 1 is preferably a hydrogen atom in that flexibility, elongation and strength are further improved. Z in formula 1 is preferably a fluorine atom in that it provides better heat resistance and chemical resistance. In formula 1, n is preferably 2 to 8, more preferably 2 to 6, and even more preferably 2, 4, or 6. When n is equal to or more than the lower limit, the mechanical properties and thermal stability of the composition are more excellent, and when n is equal to or less than the upper limit, the FAE has sufficient polymerization reactivity.

[0021] Preferred specific examples of FAE include CH2=CH(CF2)2F, CH2=CH(CF2)4F, CH2=CH(CF2)6F, CH2=CF(CF2)4F, CH2=CF(CF2)3H, etc. Among them, CH2=CH(CF2)4F (hereinafter also referred to as PFBE) is preferred because it has more excellent mechanical properties and thermal stability. The FAE may be used alone or in combination of two or more kinds.

[0022] In ETFE, the molar ratio of E units to TFE units (E units / TFE units) is preferably 30 / 70 to 60 / 40, more preferably 35 / 65 to 60 / 40. When the E units / TFE units is equal to or higher than the lower limit, the melting point of ETFE is sufficiently high, and the heat resistance and rigidity at high temperatures are excellent, and when it is equal to or lower than the upper limit, the chemical resistance is excellent.

[0023] The ratio of the other monomer units is preferably 0.7 to 5.0 mol %, more preferably 0.9 to 4.0 mol %, based on the total units constituting ETFE. When the ratio of the other monomer units is equal to or higher than the lower limit, the stress crack resistance at high temperatures is further excellent, and when it is equal to or lower than the upper limit, the melting point of ETFE is sufficiently high, and the heat resistance and rigidity at high temperatures are excellent.

[0024] ETFE preferably has a hydroxyl group at the main chain end. ETFE having a hydroxyl group at the main chain end tends to have a better affinity with additive B than ETFE having no hydroxyl group at the main chain end. When the fluororesin contains ETFE having a hydroxyl group at the main chain end as a main component, additive B can be well dispersed in the fluororesin, and it is easy to increase the tensile strength retention rate and tensile elongation retention rate described later. The main chain ends of ETFE can be confirmed by analyzing ETFE by infrared spectroscopy.

[0025] The content of hydroxyl groups at the ends of the main chain can be determined by the peaks of the overtones of the C-F bonds in the infrared absorption (IR) spectrum (e.g., 2210 cm -1 ) to the hydroxyl peak (e.g., 3540 cm -1 The area ratio of the peak of the main chain terminal hydroxyl group is preferably 1 to 50%, and more preferably 3 to 30%. When the content of the hydroxyl group at the main chain terminal is not less than the lower limit, the dispersibility of the additive B is superior, and when it is not more than the upper limit, the heat resistance is superior. The content of hydroxyl groups at the ends of the main chain can be adjusted by the molecular weight of ETFE.

[0026] The melting point of ETFE is preferably 160 to 320° C., more preferably 245 to 270° C., and even more preferably 250 to 265° C. When the melting point of ETFE is not less than the lower limit, the heat resistance and rigidity at high temperatures are excellent, and when it is not more than the upper limit, the moldability is excellent. The melting point of ETFE can be adjusted by the molar ratio of E units to TFE units, the ratio of other monomer units to all units constituting ETFE, and the like.

[0027] The fluororesin to be used may be a commercially available product, or may be one produced by a known production method. ETFE can be produced, for example, by the method described in paragraphs

[0021] to

[0025] of Patent Document 1 or the method described in paragraphs

[0036] to

[0043] of International Publication No. 2016 / 006644.

[0028] ETFE having a hydroxyl group at the main chain end can be obtained, for example, by using an alcohol as a chain transfer agent when polymerizing a monomer. Specifically, as described in paragraph

[0016] of JP2016-043566A, when an alcohol is used as a chain transfer agent, the hydroxyl group of the alcohol is introduced to the main chain end of ETFE, and ETFE having a terminal group consisting of a hydroxyl group at the main chain end is obtained.

[0029] <Additive B> A carbon-containing inorganic material is used as additive B. Even a small amount of the carbon-containing inorganic material can impart excellent flame retardancy. Examples of carbon-containing inorganic substances include carbon black, carbon nanotubes, carbon fibers, graphene, fullerene C60, and artificial diamonds. These carbon-containing inorganic substances may be used alone or in combination of two or more. As the carbon-containing inorganic substance, carbon black or carbon fiber is preferred from the viewpoint of dispersibility.

[0030] When Additive B is kept in an atmosphere of 28°C and 80% RH for 14 days and then heated in an oven at 150°C for 1 hour, the mass loss rate is preferably less than 0.3% by mass, more preferably less than 0.25% by mass, and even more preferably less than 0.2% by mass. The mass reduction rate is an index of the water absorption of additive B, and varies depending on the material and shape of additive B. The lower the mass reduction rate, the easier it is to blend with the fluororesin and disperse in the fluororesin. If the mass reduction rate is less than 0.3% by mass, additive B can be well dispersed in the fluororesin, and the tensile strength retention rate and tensile elongation retention rate described below can be easily increased.

[0031] <Other ingredients> The present composition may further contain components other than the fluororesin and additive B, as necessary, to the extent that the effects of the present invention are not significantly impaired. Examples of other components include fluorine-containing organic substances, pigments, conductors, glass fibers, glass balloons, silicon, and talc. These components may be used alone or in combination of two or more.

[0032] <Content of each ingredient> In the present composition, the content of additive B is 0.0001 to 20 mass% relative to the total mass of the present composition. When the content of additive B is equal to or more than the lower limit, the flame retardancy is excellent, and when it is equal to or less than the upper limit, the content of the fluororesin can be increased, and the composition is excellent in chemical resistance, heat resistance, weather resistance, etc. The content of additive B is preferably 0.001 mass% or more relative to the total mass of the present composition, more preferably 0.01 mass% or more, even more preferably 1 mass% or more, and is preferably 15 mass% or less.

[0033] The content of the fluororesin is 99.9999% by mass or less, preferably 99.999% by mass or less, more preferably 99.99% by mass or less, even more preferably 99.9% by mass or less, particularly preferably 99% by mass or less, and preferably 80% by mass or more, more preferably 85% by mass or more, based on the total mass of the composition. When the content of the fluororesin is equal to or more than the lower limit, the composition has excellent chemical resistance, heat resistance, weather resistance, etc., and when the content is equal to or less than the upper limit, the composition has excellent flame retardancy.

[0034] The content of other components is preferably 5% by mass or less, more preferably 3% by mass or less, and may be 0% by mass, based on the total mass of the composition.

[0035] <Characteristics of the composition> The LOI of the composition is 35% or more, preferably 37% or more. If the LOI is equal to or more than the lower limit, the composition is highly useful in applications requiring flame retardancy. The higher the LOI of the composition, the more preferable it is in terms of flame retardancy. The upper limit is not particularly limited, but is, for example, 95%.

[0036] The tensile strength of the composition is preferably 80% or more, more preferably 90% or more, of the tensile strength of the fluororesin. If the ratio of the tensile strength of the composition to the tensile strength of the fluororesin (hereinafter also referred to as the tensile strength retention rate) is equal to or more than the lower limit, additive B is well dispersed or compatible with the fluororesin, and the effect of imparting flame retardancy by additive B is easily exhibited. In addition, durability and the like can be sufficiently ensured, and the composition is excellent in practical use. The upper limit of the tensile strength retention is not particularly limited, but is, for example, 120%. The tensile strength retention rate can be adjusted by, for example, the type and content of additive B and its particle size.

[0037] The tensile strength of the composition is preferably 30 MPa or more, more preferably 35 MPa or more. If the tensile strength is equal to or more than the lower limit, the composition has excellent dispersibility. The upper limit is not particularly limited, but is, for example, 75 MPa.

[0038] The tensile elongation of the composition is preferably 80% or more, more preferably 95% or more, of the tensile elongation of the fluororesin. When the ratio of the tensile elongation of the composition to the tensile elongation of the fluororesin (hereinafter also referred to as the tensile elongation retention rate) is equal to or more than the lower limit, additive B is well dispersed or compatible with the fluororesin, and the effect of imparting flame retardancy by additive B is easily exhibited. In addition, durability and the like can be sufficiently ensured, and practicality is excellent. The upper limit of the tensile elongation retention is not particularly limited, but is, for example, 120%. The tensile elongation retention rate can be adjusted by, for example, the type and content of additive B and its particle size.

[0039] The tensile elongation of the composition is preferably 350% or more, more preferably 385% or more. When the tensile elongation is equal to or more than the lower limit, the composition has excellent mechanical properties and is more resistant to breakage when subjected to an external force.

[0040] <Method of manufacturing the present composition> The composition is produced, for example, by mixing a fluororesin and additive B. A master batch in which a part of the fluororesin and additive B are mixed in advance may be mixed with the remaining fluororesin. If necessary, other components may be mixed. The ratio of each of the fluororesin, additive B, and other components to the total mass of all the raw materials to be mixed is the same as the ratio of each of the fluororesin, additive B, and other components to the total mass of the composition.

[0041] When the fluororesin is melt-moldable, the mixing method is preferably a method in which the fluororesin, additive B, and, if necessary, other components are melt-kneaded. The melt-kneading method may be a method using a known melt-kneading device. The melt kneading device may be a device having a known melt kneading function. As the melt kneading device, a single screw extruder or a twin screw extruder, which may be equipped with a screw having a high kneading effect, is preferable, a twin screw extruder is more preferable, and a twin screw extruder equipped with a screw having a high kneading effect is particularly preferable. As the screw having a high kneading effect, a screw having a sufficient kneading effect on the melt kneading object and not applying excessive shear force can be selected. From the viewpoint of the kneading effect, the L / D of the screw is preferably 20 or more, more preferably 30 to 70. "L / D" is the value obtained by dividing the total screw length L (mm) by the screw diameter D (mm). Specific examples of the melt kneading device include a Labo Plastomill kneader (manufactured by Toyo Seiki Seisakusho Co., Ltd.) and a KZW series twin-screw kneading extruder (manufactured by Technovel Co., Ltd.).

[0042] There is no particular limitation on the method of supplying the fluororesin and additive B to the melt kneader. The fluororesin and additive B may be mixed in advance and then supplied to the melt kneader, or the fluororesin and additive B may be supplied separately to the melt kneader. The same applies to the other components.

[0043] The temperature at which the fluororesin and additive B are melt-kneaded (hereinafter also referred to as the melt-kneading temperature) is preferably set depending on the fluororesin and additive B. The melt-kneading temperature is preferably 220 to 400°C, more preferably 250 to 350°C.

[0044] The fluororesin and additive B are preferably melt-kneaded so that the tensile strength retention rate and the tensile elongation retention rate are equal to or higher than the lower limit values ​​mentioned above. For example, by increasing the melt-kneading temperature, additive B is easily dispersed in the fluororesin, and the tensile strength retention rate and the tensile elongation retention rate tend to be high. By decreasing the melt-kneading temperature, the thermal decomposition of the fluororesin is not easily promoted, and the heat resistance of the obtained composition is further improved. By increasing the extrusion shear rate, additive B is easily dispersed in the fluororesin, and the tensile strength retention rate and the tensile elongation retention rate tend to be high. By decreasing the extrusion shear rate, decomposition of the main chain can be suppressed. Increasing the residence time of the material to be melt-kneaded in the melt-kneading device makes it easier for Additive B to disperse in the fluororesin, and tends to increase the tensile strength retention rate and the tensile elongation retention rate. Increasing the residence time makes it harder for the thermal decomposition of the fluororesin to be promoted, and the heat resistance of the resulting composition is further improved.

[0045] <Application> The composition can be used for, for example, electric wire coating materials, pipe linings, semiconductor manufacturing equipment parts, semiconductor structural materials, release films, packaging films, drug transport tubes, packings, gaskets, pump linings, automobile fuel lines, tubes, blow molded containers, high frequency bases, high frequency insulating parts, materials for 3D printers, architectural membrane structures, air filters, hollow fibers, and plastic screws. However, the uses of the composition are not limited to these.

[0046] <Action and effect> The composition contains a carbon-containing inorganic substance as additive B in a content of 0.1% by mass or more and has an LOI of 35% or more, so that it has excellent flame retardancy. In addition, the content of additive B is 20% by mass or less, so that it has excellent chemical resistance. EXAMPLES

[0047] The present invention will be specifically described below with reference to examples, but the present invention is not limited to the description of the following examples. Example 1 is a comparative example, and Examples 2 to 6 are working examples.

[0048] [Evaluation method] <loi> The LOI was measured in accordance with JIS K 7201-2:2007.

[0049] <Mass reduction rate of additives> The additive was kept in an atmosphere of 28°C and 80% RH for 14 days, and then its mass M1 (g) was measured. The additive was placed in an oven at 150°C and heated for 1 hour, after which its mass M2 (g) was measured and the mass loss rate was calculated using the following formula. The smaller the mass loss rate, the lower the water absorption rate of the additive. Mass reduction rate (%)=(M1-M2) / M1×100

[0050] <Tensile properties> (Preparation of test specimens) The fluororesin composition was melt molded at 320° C. to prepare a pressed sheet of 200 mm×200 mm×1 mm thickness. The obtained pressed sheet was punched into a JIS K 6251 No. 3 dumbbell shape and left to stand at 23° C. and 50% RH for 24 hours to obtain test piece A. Test piece B was obtained in the same manner as above, except that a fluororesin blended in a fluorine-containing resin composition was used instead of the fluororesin composition.

[0051] (Tensile test) For each of the obtained test pieces A and B, a tensile test was carried out using a Strograph R-2 (manufactured by Toyo Seiki Co., Ltd.) in accordance with JIS K 6251 at 200 mm / min to determine the tensile strength (MPa) and tensile elongation (%).

[0052] (Tensile strength retention rate, tensile elongation retention rate) From the tensile strength and tensile elongation thus determined, the tensile strength retention rate and the tensile elongation retention rate were calculated according to the following formulas. Tensile strength retention rate (%) = Tensile strength of test piece A / Tensile strength of test piece B × 100 Tensile elongation retention rate (%) = Tensile elongation of test piece A / Tensile elongation of test piece B × 100

[0053] [Materials used] ETFE: A synthetic product obtained in Synthesis Example 1 described below. Additive master batch: Pellets of a mixture of ETFE and carbon black (CB) (CB content: 15% by mass relative to the total mass of the pellets).

[0054] [Synthesis Example 1] After degassing the inside of a 430-liter stainless steel autoclave, 417.2 kg of CF3(CF2)5H, 3.8 kg of methanol, and 1.9 kg of perfluorobutylethylene (hereinafter referred to as "PFBE") were charged, and the temperature was raised to 66°C while stirring, and a mixed gas of TFE / E=83 / 17 (mol%) was introduced until the pressure reached 1.5 MPa (gauge). Next, 1048 g of a CF3(CF2)5H solution with a concentration of 1 mass% of tert-butyl peroxypivalate was injected into the autoclave to start polymerization. During polymerization, a mixed gas of TFE / E=54 / 46 (mol%) and an amount of PFBE equivalent to 1.4 mol% relative to the mixed gas were continuously added so that the pressure inside the autoclave was 1.5 MPa (gauge). When the amount of the mixed gas added reached 27 kg, the autoclave was cooled, and a part of the residual monomer gas was purged to obtain a slurry 1 of ETFE. 120 kg of the obtained slurry 1 was stored in a storage tank, and the obtained ETFE slurry was charged into a 220 L (liter) granulation tank charged with 77 kg of water. The temperature was then raised to 105°C with stirring, and the solvent was distilled off while granulating to recover powdery ETFE dried material 1, thereby obtaining ETFE having hydroxyl groups at the ends of its main chain. The copolymerization composition of the obtained ETFE was E unit / TFE unit (molar ratio) = 54.1 / 45.9, PFBE unit was 1.4 mol% relative to the total units constituting ETFE, the melting point was 259°C, and MFR was 9.8g / 10min. The mass ratio of hydrogen atoms / fluorine atoms calculated from the copolymerization composition was 4 / 96. The content of hydroxyl groups at the main chain terminals was 9% relative to the overtone peak of the CF bond in terms of the area ratio of the ETFE IR spectrum.

[0055] [Examples 1 to 6] ETFE and the additive master batch were mixed so that the final additive master batch content was the value shown in Table 1, and kneaded in a twin-screw extruder to obtain a fluororesin composition. The additive master batch content in terms of CB is also shown in Table 1. The additive master batch and CB contents are each a ratio (mass%) to the total mass of the fluororesin composition. The tensile properties and LOI of the resulting fluororesin composition were evaluated, and the results are shown in Table 1.

[0056] [Table 1]

[0057] Examples 2 to 6 had higher LOI and better flame retardancy than Example 1 consisting of only a fluororesin. In addition, because the content of Additive B was 20 mass% or less, it can be seen that the chemical resistance of the entire fluororesin composition was excellent.< / loi>

Claims

1. A fluororesin composition comprising a fluororesin and an additive that imparts flame retardancy to the fluororesin, the additive is a carbon-containing inorganic material, the content of the additive is 0.0001 to 20% by mass based on the total mass of the fluororesin composition, A fluororesin composition having a limit oxygen index of 35% or more.

2. 2. The fluororesin composition according to claim 1, which has a tensile strength of at least 80% of the tensile strength of said fluororesin and a tensile elongation of at least 80% of the tensile elongation of said fluororesin.

3. 3. The fluororesin composition according to claim 1, wherein the additive is kept in an atmosphere of 28°C and 80% RH for 14 days and then heated in an oven at 150°C for 1 hour, and the mass loss rate of the additive is less than 0.3% by mass.

4. the fluororesin comprises a partially fluorinated resin, The fluororesin composition according to any one of claims 1 to 3, wherein the partially fluorinated resin has the highest content among all the fluororesins contained in the fluororesin composition.

5. the fluororesin comprises a copolymer having a unit based on tetrafluoroethylene and a unit based on ethylene, The fluororesin composition according to any one of claims 1 to 4, wherein the content of the copolymer is the highest among all the fluororesins contained in the fluororesin composition.

6. The fluororesin composition according to claim 5 , wherein the copolymer has a hydroxyl group at a main chain terminal.

Citation Information

Patent Citations

  • High-flame-retardant black ethylene-tetrafluoroethylene copolymer coating and preparation method thereof

    CN111574890A